Additional description and geographic distribution of the splitfin ocean-bass Synagrops atrumoris from southwestern Taiwan - Huang, Yu-Shan; Chen, Hong-Ming (Zootaxa, 2025)
The splitfin ocean-bass Synagrops atrumoris belonging to the Family Synagropidae is newly recorded from Dong-gang Fishing Port, Pingtung County, southwestern Taiwan. In this study, we expand the geographical distribution and provide a series of detailed additional dental and osteological descriptions of this species. Fresh color photographs, radiographs, the description of the structure of the proximal-middle radial of the first anal-fin pterygiophore, dentition illustration of this specimen, and comparisons with the congener S. japonicus are also provided herein.